Media Aid Beyond the Factual: Culture, Development, and Audiovisual Assistance - Pearson, Benjamin (Global Media Journal - German Edition, 2015)
This paper discusses audiovisual assistance, a form of development aid that focuses on the production and distribution of cultural and entertainment media such as fictional films and TV shows. While the first audiovisual assistance program dates back to UNESCO’s International Fund for the Promotion of Culture in the 1970s, the past two decades have seen a proliferation of audiovisual assistance that, I argue, is related to a growing concern for culture in post-2015 global development agendas. In this paper, I examine the aims and motivations behind the EU’s audiovisual assistance programs to countries in the Global South, using data from policy documents and semi-structured, in-depth interviews with Program Managers and administrative staff in Brussels. These programs prioritize forms of audiovisual content that are locally specific, yet globally tradable. Furthermore, I argue that they have an ambivalent relationship with traditional notions of international development, one that conceptualizes media not only as a means to achieve economic development and human rights aims, but as a form of development itself.